Simulation of sea surface current from RADARSAT- SAR data by using robust model - Marghany, Maged (2007)
This paper was utilized robust model to simulate sea surface current pattern. The horizontal surface velocity model was modified based on the Doppler frequency theory to model the sea surface current velocity. The robust model was implemented on the SAR image at two different modes (Wide-3 and Standard-2). The results of the study were validated using real time ocean current measurements by using AWAC equipment.